2011
DOI: 10.1073/pnas.1107861108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically inhibited order in a diamond-lattice antiferromagnet

Abstract: Frustrated magnetic systems exhibit highly degenerate ground states and strong fluctuations, often leading to new physics. An intriguing example of current interest is the antiferromagnet on a diamond lattice, realized physically in A-site spinel materials. This is a prototypical system in three dimensions where frustration arises from competing interactions rather than purely geometric constraints, and theory suggests the possibility of unusual magnetic order at low temperature. Here, we present a comprehensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
43
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 48 publications
5
43
2
Order By: Relevance
“…Theoretical studies have also shown that with this NNN interaction the normal A-site spinel can exhibit various degenerate magnetic ground states [11]. It should be noted that some A-site normal spinels such as FeAl2O4 and CoAl2O4 are known to display glass-like behavior due to the competition between the NN and NNN interactions for the diamond structure of the A-sublattice [11,12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies have also shown that with this NNN interaction the normal A-site spinel can exhibit various degenerate magnetic ground states [11]. It should be noted that some A-site normal spinels such as FeAl2O4 and CoAl2O4 are known to display glass-like behavior due to the competition between the NN and NNN interactions for the diamond structure of the A-sublattice [11,12,13].…”
mentioning
confidence: 99%
“…Among these TAl2O4 systems, CoAl2O4 is the most frustrated material lying close to a quantum critical point of an antiferromagnetic state [12,16].…”
mentioning
confidence: 99%
“…Until now, several series of A-site spinels, in which the magnetic A ions form a diamond lattice, have been investigated, including: the cobaltates Co 3 O 4 and CoRh 2 O 4 16 ; the aluminates M Al 2 O 4 with M = Fe, Co, Mn [17][18][19][20] ; and the scandium thiospinels M Sc 2 S 4 with M = Fe, Mn 21 . For the spinels with Fe 2+ at the A-site, the e g orbital angular momentum of Fe 2+ is active, making the pure spin J 1 -J 2 model inadequate 22 .…”
mentioning
confidence: 99%
“…The exchange term J(Q) describes interactions betweens spins on opposite sublattices and J'(Q) describes interactions between spins on the same sublattice. The absolute value |J(Q)| must be taken because the honeycomb lattice is non-Bravais, like the diamond lattice [39]. We include first neighbor exchange interactions J 1 for spins that are on opposite sublattices, second neighbor interactions J 2 for spins that are on the same sublattice, and exchange interactions between nearest neighbors in different honeycomb layers J c for spins that are on opposite sublattices.…”
mentioning
confidence: 99%